Cover Feature: Effect of Electrolyte and Electrode Configuration on Cu‐Catalyzed Nitric Oxide Reduction to Ammonia (ChemElectroChem 5/2022). Issue 5 (1st February 2022) - Krzywda, Piotr M.; Paradelo Rodríguez, Ainoa; Benes, Nieck E.; Mei, Bastian T.; Mul, Guido
Abstract : The Cover Feature illustrates the cross section of a Ti hollow fiber electrode modified with copper, enabling electrochemical reduction of nitric oxide to ammonia. The inside of the electrode is filled with NO, which is purged through the porous wall of the electrode to facilitate NO reduction at the gas‐solid‐liquid interface with high faradaic efficiency. More information can be found in the Article by P. M. Krzywda et al .